Welcome to Oz 2.0 : a cinematic approach to digital still photography with Photoshop - Versace, Vincent (New Riders, 2011)
A guide to creating the perfect photograph covers how to approach an image, workflow, and the use of light, gesture, shape, time, and color, while using Photoshop to bring out the important aspects of the photograph.